Spotlight on Data Self-Service Data-Reliable Data Pipelines at Intuit with Sandeep Uttamchandani - Uttamchandani, Sandeep, 1979- (O'Reilly Media, Inc., 2019)
There's no scarcity of raw data within enterprises. So why can't analysts and data scientists generate insights fast enough to keep up with business needs? Extracting insights depends on data engineering and source teams to ingest, clean, catalog, debug, and deploy, slowing down the overall process. One solution: make the data platform self-serve for analysts and data scientists. And Intuit is doing just that. In this Spotlight on Data, Sandeep Uttamchandani gives an overview of the self-serve design patterns and frameworks Intuit has built to expedite time to reliable insights-its metric of success. You'll learn how the company uses circuit breakers in data pipelines to make data availability in dashboards a function of the data quality, radically reducing debugging time. Recorded on September 16, 2019. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Data, you'll learn about, discuss, and debate the tools, techniques, questions, and quandaries in the world of data. You'll discover how successful companies leverage data effectively and how you can follow their lead to transform your organization and prepare for the Next Economy.